Development of Student’s Mission Learning Media on The Addition and Subtraction of Integer - Nita Fatma Fauziah; Arum Sulistyo Pawestri (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2022)
The success of the students in learning addition and subtraction of integer can be influenced by some factors, one of them is how the teacher delivering those materials. One of joyful learning in teaching addition and subtraction of integer is by using educational games. This research purpose is to develop a valid and practical learning media, which is called educational game